Assessing Fire Severity in Semiarid Environments with the DNBR and RDNBR Indices - Ghermandi, Luciana (2019)
Fil: Ghermandi, Luciana. Laboratorio Ecotono, Instituto Nacional de Investigaciones en Biodiversidad y Medioambiente (CONICET - UNCo); Argentina.